Distributed seeing: Algorithms and the reconfiguration of the workplace, a case of 'automated' trading - Willems, Thijs; Hafermalz, Ella (Information and organization, 2021)
Contemporary organizations increasingly rely on digital technologies structuring how work gets done. Algorithms in particular are fundamental for such technologies. Management literature on digital transformation has studied how algorithms either automate or augment work. In doing so, this literature treats algorithms as largely independent from existing work practices. This paper, on the contrary, theorizes and empirically illustrates how algorithms transform the workplace in a spatiotemporal sense by introducing a new epistemic vantage point through which work is understood. We do so by drawing on previous work on reconfiguration and ‘Ways of Seeing’, and through a qualitative case study on sports trading. Our analysis shows that traders and algorithms each perceive and see the market in specific, though incomplete ways. Since this market is partly virtual and constituted via a range of heterogeneous actors, ‘seeing’ the market entails knowing its distributed nature and pulling spatiotemporal distant elements together. Our paper contributes to the literature on the effects of algorithms on work by putting forward the conceptual lens of ‘distributed seeing’. This highlights that digital transformation is more than an instrumental optimization process by automating or augmenting tasks with technology but that it actively reconfigures the work to be done. We show that digital transformation 1) is reciprocal and thus irreversible; 2) patchworked and thus requires mending work; 3) introduces new organizational vulnerabilities. •Management literature studied how algorithms automate or augment work, thereby largely neglecting how work reconfigures.•The paper shows how algorithms transform work practices, and how knowledge and expertise become spatiotemporally distributed.•Algorithms introduce new ways of seeing into the workplace which need to be aligned.•Digital transformation is more than the instrumental restructuring of work but reconfigures it